Avaliação da potencialidade para implantação de um empreendimento com foco no agroturismo em propriedades rurais nos municípios de Cascavel e Braganey no Paraná - Dessanti, Jucé Marcos (2023)
Agritourism is understood as an activity that provides a complementary source of income for properties based on family farming, seeking diversification between agricultural and non agricultural activities, which includes the provision of accommodation, food, entertainment, and leisure for tourists who are enthusiasts of the countryside and nature. The main objective of this research was to carry out a survey of the current situation and evaluate the potential of rural properties to undertake in the agrotourism segment in the municipalities of Cascavel and Braganey, state of Paraná. As a way of including income to family farming, it was sought to adapt the instrument proposed by Pedreira (2006) and identify potentialities with a conclusive report of the current situation and possible improvements that were raised in the research. The methodological aspects are qualitative and descriptive, which were defined by means of a methodological script for evaluating the agrotourism potential at the rural property level, adapted from Pedreira (2006), applied in rural properties, as a structured questionnaire, in addition to the participant observer technique in a systematic way, being also a case-study by the researchers, with the instrument adapted for the region, being the first research carried out in the region for the implementation of agrotourism, diagnosing indicators that generated the data and essential information about the characteristics and attributes of activities of the properties. The expected results were the identification and diagnosis of potential attributes of rural properties A and B to undertake in agrotourism. The characteristics of agritourism were found with the important factors from the properties to the owners and the modifications and adaptation of Pedreira's instruments (2006) were approved.